Disharmony of Regulations as a Normative Impact of the Enactment of the New Criminal Code - Raymundus Loin; Edmundo Octovianus Loin; Marlina Samosir (Bacarita Law Journal, 2026)
The enactment of the new Criminal Code marks a major change in the Indonesian criminal law system. However, this reform must contend with various existing sectoral laws, thus creating the potential for regulatory disharmony due to differences in regulations and overlapping norms. This study aims to determine the occurrence of regulatory disharmony as a normative impact of the enactment of the new Criminal Code in relation to various existing sectoral laws in Indonesia and to determine the overlapping regulations and application of the principle of lex specialis derogat legi generali between the new Criminal Code and specific laws contributing to the emergence of regulatory disharmony in the national criminal law system. This study uses normative juridical legal research, where the data is sourced from secondary data. The research results indicate that regulatory disharmony as a normative impact of the enactment of the new Criminal Code occurs because a number of its criminal provisions are not fully aligned with existing sectoral laws. Differences in regulations, the scope of offenses, and the construction of sanctions give rise to overlapping norms and unclear application of the lex specialis principle, thus creating legal uncertainty in the practice of criminal law enforcement in Indonesia. The overlapping regulations between the new Criminal Code and special laws, coupled with the unclear application of the lex specialis derogat legi generali principle, are significant factors triggering regulatory disharmony. Uncertainty in determining which norms should be prioritized in dual-regulated offenses leads to differences in interpretation among law enforcement, opens up room for inconsistent decisions, and disrupts legal certainty in the national criminal law system.